FORMATION OF COMPLETE REFLEX CONSTRUCTIONS OF FUTURE PEDAGOGUE IN THE EDUCATIONAL ENVIRONMENT OF HIGHER EDUCATION - ZHELANOVA , VIKTORIYA (Journal of Vasyl Stefanyk Precarpathian National University, 2019)
The article substantiates the relevance and expediency of the implementation of reflexively oriented education of a future teacher in a modern institution of higher education. The essence of reflexive constructs of the future teacher as unity of reflexive competence and reflexively deterministic constructs is revealed. The reflexive competence of the future teacher is defined as professional-personal metaquality and is represented in two planes: 1) as an independent construct; 2) as a determinant, which determines the development of reflexively saturated constructs. In the context of reflexive determination, the motivational, semantic and subjective fields of personality are presented. The directions of the process of transformation of components of reflexive competence, as well as motives, meanings, professional subjectivity in the plane of their reflexive determination are revealed. The phenomenon of the educational environment of the institution of higher education is analyzed and attention is focused on its reflexive orientation. The logic and peculiarities of the formation of reflexive constructs of the future teacher in accordance with the phases of the environment (adaptation to the environment, the active reproduction of the environment by students, the active influence of students on the environment and the independent creation of the environment) are highlighted.